Retrospective evaluation of the prognostic utility of plasma lactate concentration and serial lactate measurements in dogs and cats presented to the emergency room (January 2012 – December 2016): 4863 cases. Issue 1 (3rd August 2021) - Saint‐Pierre, Laurence M.; Hopper, Kate; Epstein, Steven E.
Abstract: Objective: To determine the prognostic significance of plasma lactate concentration, plasma lactate clearance, and delta lactate in dogs and cats presented to an emergency room (ER). Design: Retrospective study. Setting: University teaching hospital. Animals: A total of 8, 321 animals with a plasma lactate concentration measured with 4, 863 presenting to the ER and 1, 529 dogs and 444 cats having a measurement within 4 hours of admission. Interventions: None. Measurements and main results: Plasma lactate concentration of dogs and cats presented to a university teaching hospital was retrospectively evaluated. Of dogs and cats with a plasma lactate concentration measured within 4 hours of admission to the ER, hyperlactatemia was common, and the prevalence of hyperlactatemia for dogs 78% (361/462) and cats 67% (78/116) was highest when evaluated within the first 30 minutes following admission. The distribution of patient's plasma lactate concentration was significantly higher in non‐survivors compared to survivors at all time points evaluated ( P < < 0.001). Both lactate clearance ( P = 0.010) and delta lactate ( P = 0.013) were significantly different between survivors and nonsurvivors. A delta lactate > 4.5 mmol/L was 100% (95% CI: 95 to 100%) specific for nonsurvival in patients with hyperlactatemia measured within 1 hour of admission to the ER. The most common cause of hyperlactatemia was shock in dogs (24%) and urinary tract diseases in cats (22%). Shock was associated with the highest mortality rate in both dogs (61%) and cats (77%). Hyperlactatemia was significantly associated with increased mortality for dogs with shock ( P = 0.001), respiratory diseases ( P = 0.022), diabetes mellitus ( P = 0.018), and liver dysfunction ( P = 0.006). Conclusions: Hyperlactatemia was associated with mortality in both dogs and cats when measured at any time point in the 4 hours following admission to the ER. Serial lactate measurement may also be a valuable tool to guide clinical management decisions.